THE POLICY OF CLEAN WATER SUPPLY BY IDENTIFYING CRITICAL AREAS IN BANYUWANGI, EAST JAVA - Amir, M.H.T. (Acta Scientiae et Intellectus, 2024)
This study aimed to determine the policy of clean water supply in area of clean water crisis in Banyuwangi. The study was conducted in 5 subdistricts, namely Wongsorejo subdistrict, Licin subdistrict, Songgon subdistrict, Kalibaru subdistrict and Pesanggaran subdistrict. Two analyses were conducted in this study, namely; the analysis of the clean water needs and the analysis of clean water availability. Four parameters were used in this study, namely: a) forest area; b) rainfall; c) total area; and d) population. The results showed that among those five subdistricts in Banyuwangi, only Kalibaru subdistrict was considered as area with clean water crisis due to its population of 61,820 inhabitants within an area of 18,741.80 km2. The result of clean water needs measurement (K) was 353,870.9 m3/year and groundwater recharges (RC) as 556,633 m3/year (the clean water needs has not been fulfilled). To this problem, the local governement of Banyuwangi should do reforestation of 0.78% denuded forest in order to cover 30% of forest area in Kalibaru subdistrict according to the Law of the Republic of Indonesia Number 26 Year 2007 about spacial planning. Therefore, the role of forests was extremely needed in order to serve the environment both socially and economically and give advantages to the local community.